Boosting School Administrator Confidence When Evaluating Special Educators Through District Support and Training (Journal of School Administration Research and Development, 2020)
This current study is an exploratory, secondary data analysis of a survey assessing training, district support, and confidence of school administrators when it comes to special education teacher evaluation. The present study specifically examines (a) if the influence of district training regarding special education teachers influences the confidence of school administrators to evaluate and observe special education teachers, (b) if administrators with a general education credential differ from administrators with a special education credential regarding the type of district support needed to better evaluate special education teachers; and (c) if possessing a special education credential influences an administrator’s confidence when evaluating both general and special education teachers at their school site. Results indicated that district training regarding special education teacher evaluation increased administrator confidence and that administrators with general education credentials desired more district support overall than did their counterparts with a special education credential. The data also showed that administrators with a special education credential felt significantly more confident evaluating special education and general education teachers than did their counterparts from general education backgrounds. Implications for the field of special education evaluation and future directions are discussed.